Aplikasi Model Fisika Tanah untuk Prediksi Pergerakan Air dan Nutrisi pada Sistem Pertanian Modern - Lase, Edwin Kaskar Jaya; Ndruru, Eka Julianti (CV. SINAR HOWUHOWU, 2024)
This research aims to develop a soil physics model to predict the movement of water and nutrients in modern agricultural systems. This model includes water flow modeling using the Richards equation as well as nutrient distribution using an advection-dispersion approach. Soil data was obtained through direct measurements in the field and laboratory tests, while the model was validated using field data to evaluate prediction accuracy. The research results show that soil texture and water capacity greatly influence water flow and nutrient distribution in the soil, with fairly high model accuracy values ​​(R² = 0.89 for water flow and MAE = 0.12 for nutrient distribution). The use of this model provides guidance in more efficient scheduling of irrigation and fertilizer applications, supporting sustainable resource management. These findings show that soil physics models can play an important role in precision agriculture to increase land productivity and maintain environmental sustainability